Diagnostic Value of Low-Dose 256-Slice Spiral CT Angiography, MR Angiography, and 3D-DSA in Cerebral Aneurysms - Feng, Yan (Dis Markers, 2020)
OBJECTIVE: To evaluate the diagnostic value of low-dose 256-slice CT angiography (CTA), MR angiography (MRA), and three dimensional-digital subtraction angiography (3D-DSA) in cerebral aneurysms. METHODS: CTA, MRA, and 3D-DSA were performed in all enrolled patients to explore the diagnostic significance of the three different examinations. RESULTS: There were 92 aneurysms confirmed during DSA and surgery in 79 patients. The diagnostic coincidence rates of DSA, CTA, and MRA were 96.7%, 89.1%, and 86%, respectively. The diagnostic coincidence rates of CTA and MRA were lower than those of DSA. The detection rate of CTA for aneurysms less than 3 mm in diameter was higher than that of MRA. CONCLUSION: CTA, DSA, and MRA have their own advantages and disadvantages in the diagnosis of cerebral aneurysms. They all have the diagnostic value for aneurysms.